Toxic organizational cultures and leadership how to build and sustain a healthy workplace - Hetrick, Susan (London Routledge Taylor & Francis Group, 2023)
Toxic organisational cultures and leadership have led to major reputational failures, with the greatest impact felt by the people who dedicate their careers to working for these organisations. And yet organizations do not become toxic overnight. They do not consciously set out to break rules and regulations, nor do they actively seek wrongdoing. This book defines toxic culture, explains how toxic cultures emerge over time, and provides practical approaches supported by in-depth research for overcoming a toxic culture at the individual, team, and organizational level. Pragmatic and applicable, the book provides a call to action that can be applied in any type of organization. Whilst the role of leadership in toxic cultures is acknowledged, the book sets out four distinct stages to embedding toxic cultures and draws on examples from leading organizations and companies to illustrate each stage. The book then identifies interventions and levers that can be implemented by executives, boards, and HR practitioners to prevent toxicity and to change toxic cultures back to healthy, positive workplaces. Drawing on research and interviews with senior HR leaders and executives, the book provides: - An understanding of the four stages of toxic cultures and the impact of performance pressures in driving toxicity - An appreciation of the role of senior leadership and personality traits - Practical tools and guidance on interventions for practitioners to build and sustain a healthy and positive workplace Senior executives, HR and organisational development practitioners in local and global organisations spanning a range of industry sectors will find this book invaluable. The book is also highly relevant to consultants working in the field of corporate culture and change"--
Includes bibliographical references and index.
Keywords: Corporate culture; Employee morale; Leadership; Organizational behavior; Organizational change